(3GdGSGdjH hGdeYGjjQ GdMeGFjI GdLOjOI aj GdJLGQI GdOhdjIs - (3Hf YHO GdYRjR(B, (3SajGfs ((3GdLRGFQ(B:s (3GdecJH GdLGeYj GdMOjKs, 2016)
(3aj gPG GdcJGH (B: (3GdaUd GdGhd GdGWGQ GdfXQj hGdNdajI GdJGQNjI dSjGSI hCSGdjH GdJLGQI GdGOhdjI ChdG (B: (3YehejGJ heaGgje Mhd GdJLGQI GdOhdjI GdeWdH GdGhd (B: (3eGgjI GdJLGQI GdOhdjI hCgejJgG GdeWdH GdKGfj (B: (3Cge GdfXQjGJ GdeGdeaSQI ddJLGQI GdOhdjI GdeWdH GdKGdK GdYhGed GdeDKQI aj GdJLGQH GdOhdjI hGSHGH GdJNUU GdOhdj KGfjG (B: (3GdGSS GdfXQjI hGdNdajI GdJGQNjI dSjGSGJ GdJLGQI GdOhdjI GdeWdH GdGhd (B: (3eGgjI GdSjGISI GdJLGQjI hCgOGagG GdeWdH GdKGfj (B: (3deMI JGQNjI Yf GdSjGSI GdJLGQjI GdeWdH GdKGdK (B: (3CfhGY GdSjGSGJ GdJLGQjI KGdKG (B: (3fXQI GdefXeGJ GdGbJUGOjI GdOhdjI hGdGbJUGO GdGSdGej dSjGSI GdJLGQI GdOhdjI GdeWdH GdGhd (B: (3fXQI efXeI GdJLGQI GdOhdjI ddSjGSGJ GdJLGQjI GdOhdjI GdeWdH GdKGfj GdSjGSGJ GdJLGQjI aj Xd GdGJaGbjGJ HjQjJhf hhOR GdeWdH GdKGdK (B: (3GdSjGSIGJ GdJLGQjI ef hLgI GdfXQ GdGSdGejI GdaUd GdKGfj (B: (3GdGSGdjH GdMeGFjI GdLOjOI aj GdJLGQI GdOhdjI ChdG (B: (3GdGSS GdJWHjbjI ddCSGdjH GdMeGFjI aj GdJLGQI GdOhdjI GdeWdH GdChd (B: (3GdCSS hGdCSGdjH GdSYQjI GdeWdH GdKGfj (B: (3GdCSS hGdCSGdjH GdcejI hGdJfXjejI GdeWdH GdKGdK GdGSS hGdGSGdjH GdGOGQjI KGfjG GdGSGdjH GdMeGFjI GdLOjOI hCKQgG Ydi GdGbJUGOjGJ GdfGejI GdeWdH GdChd eGgjI heVehf GdCSGdjH GdMeGFjI GdLOjOI GdeWdH GdKGfj (B: (3CfhGY GdCSGdjH GdMeGFjI GdLOjOI GdeWdH GdKGdK GdOhd GdfGejI hGdCSGdjH GdMeGFjI GdLOjOI KGdKG (B: (3GdGSGdjH GdMejGFjI GdLOjOI aj Xd GdCReI GdGbJUGOjI GdYGdejI GdeWdH GdGhd GdGReI GdGbJUGOjI GdYGdejI GdeWdH GdKGfj GdCSGdjH GdMeGFjI GdLOjOI GdfGJLI Yf GdGReI GdGbJUGOjI GdYGdejI GdeWdH GdKGdK (B: (3GdGTJQGWGJ GdHjFjI cCSdhH MeGFj HGdGReGJ GdGbJUGOjI GdYGdejI GdaUd GdKGdK (B: (3GdGTJQGWGJ GdHjFjI cCSdhH MeGFj LOjO aj GdJLGQI GdOhdjI ChdG ehbY GdHYO GdHjFj aj fXQjI GdJLGQI GdOhdjI GdeWdH GdGhd (B: (3ecGfI GdHjFI aj GdacQ GdGbJUGOj GdeWdH GdKGfj GdHYO GdHjFj aj fXQjI GdJLGQI GdOhdjI GdeWdH GdKGdK (B: (3JCKjQ GdeHGOdGJ GdJLGQjI GdOhdjI Ydi GdHYO GdHjFj KGfjG GdeYGjjQ hGdeJWdHGJ GdHjFjI cCMO Cge GdYhGFb ZjQ GdLeQcjI aj GdJLGQI GdOhdjI GdeWdH GdChd eGgjI GdGOhGJ hGdSjGSGJ GdHjFjI GdeWdH GdKGfj (B: (3CfhGY hUhQ GdeYGjjQ hGdGTJQGWGJ GdHjFjI hJCKjQgG Ydi GdbOQI GdJfGaSjI ddOhd GdeWdH GdKGdK (B: (3bjGS CKQ GdeYGjjQ hGdGTJQGWGJ GdHjFjI Ydi GdJLGQI GdOhdjI KGdKG (B: (3JCKjQ GdGTJQGWGJ GdHjFjI Ydi GdGbJUGO GdhWfj GdLRGFQj GdeWdH GdGhd (B: (3GdbOQI GdGfJGLjI GdeMdjI ddCbJUGO GdhWfj GdLRGFQj GdeWdH GdKGfj (B: (3CKQ GdeYGjjQ hGdGTJQGWGJ GdHjAjI Ydi GdeJYGedjf GdGbJUGOjf GdeWdH GdKGdK (B: (3GdeTGcd hGdMdhd GdcajdI HJSgjd faGP GdUGOQGJ GdLRGFQjI Edi GdGShGb GdOhdjIs
(3edGMb U(B.247-260 (3HjHdjhZQGajG U(B. 261 -279 (3GdLOGhd hGdGTcGd U(B.281-283s
Keywords: (3GdGJaGbjGJ GdMeGFjIs; (3GdGReI GdGbJUGOjI GdYGdejIs; (3GdefXeGJ GdYGdejIs; (3JLGQI NGQLjIs